“MAGIC GARDEN" OF POETIC ART IN THE AESTHETICALLY LINGVO-BEAUTIFUL MEASURING - Голянич, М. І.; Бабій, І. Ф. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
A review on the monograph of Malenco O. is O. Lingvo-estetichna interpretation of bouttya in Ukrainian poetic movotvorchosti (from folk-lore to postmodernou): Monograph / Helen Malenco. - Kharkov, 2010. - 488 p.